The crystal arthropathies. Issue 11 (November 2013) - Jones, Robert A; Quilty, Brian
Unlike many other forms of inflammatory arthritis, the crystal arthropathies are routinely diagnosed and managed in primary care. Gout, in particular, is relatively commonplace and rates of other types of crystal-related arthritis are predicted to increase. These are, therefore, conditions that GPs and trainees will regularly encounter during routine practice. While the clinical features and pathophysiology of gout and pseudo-gout are well described, the long-term treatment goals and options of management are often less well understood, and opportunities to assess for associated co-morbidities can easily be missed. GPs can be central in optimising management by promptly and appropriately addressing acute symptoms, preventing recurrent attacks, minimising disability and work absences, reducing cardiovascular risk factors, improving general health and enhancing quality of life.